Variability of cell wall recalcitrance and composition in genotypes of Miscanthus from different genetic groups and geographical origin - Iacono, Rosario; Slavov, Gancho T.; Davey, Christopher L.; Clifton-Brown, John; Allison, Gordon; Bosch, Maurice (Frontiers in Plant Science, 2023)
Miscanthus is a promising crop for bioenergy and biorefining in Europe. The improvement of Miscanthus as a crop relies on the creation of new varieties through the hybridization of germplasm collected in the wild with genetic variation and suitable characteristics in terms of resilience, yield and quality of the biomass. Local adaptation has likely shaped genetic variation for these characteristics and is therefore important to quantify. A key biomass quality parameter for biorefining is the ease of conversion of cell wall polysaccharides to monomeric sugars. Thus far, the variability of cell wall related traits in Miscanthus has mostly been explored in accessions from limited genetic backgrounds. Here we analysed the soil and climatic conditions of the original collection sites of 592 Miscanthus genotypes, which form eight distinct genetic groups based on discriminant analysis of principal components of 25,014 single-nucleotide polymorphisms. Our results show that species of the genus Miscanthus grow naturally across a range of soil and climate conditions. Based on a detailed analysis of 49 representative genotypes, we report generally minor differences in cell wall characteristics between different genetic groups and high levels of genetic variation within groups, with less investigated species like M. floridulus showing lower recalcitrance compared to the other genetic groups. The results emphasize that both inter- and intra- specific variation in cell wall characteristics and biomass recalcitrance can be used effectively in Miscanthus breeding programmes, while also reinforcing the importance of considering biomass yield when quantifying overall conversion efficiency. Thus, in addition to reflecting the complexity of the interactions between compositional and structural cell wall features and cell wall recalcitrance to sugar release, our results point to traits that could potentially require attention in breeding programmes targeted at improving the Miscanthus biomass crop.